Studi Literatur: Strategi Entrepreneur Memulai Bisnis - Herwan Nafil; Zuhrinal M Nawawi (Universitas Muhammadiyah Sumatera Utara, 2021)
This research is a literature study that discusses how entrepreneurs start a business strategy. The first focal point in an entrepreneur starting a business is whether he sees a business opportunity around him or not. Entrepreneurship is an important part of the economy of a nation, especially a developing nation. This research is a literature study in qualitative research on how entrepreneurs start a business. There are several ways to start a business, for example in the case of property, namely: looking for land, making drawings and RAB, looking for contractors, and sharing profits with land owners. Some suggestions for those of you who are dedicated and fully committed to starting a new business, namely: find a co-founder who can keep you balanced, schedule a fixed time and day for startup, and choose a business idea that has a longer vision.